Study on shared right turn/straight lanes at signalised junctions - Sam, Wei Jing (2014)
At major junctions in Singapore, typical lanes that can be found include the left turn lane, the straight lane, the right turn lane, and occasionally a shared straight/right turn lane. A quick bit of research shows that this arrangement of having a lane service both the through traffic and right turners while both directions have additional lanes dedicated to each directions on either side of the shared lane is fairly uncommon. It is both a flexible system, theoretically allowing more vehicles to utilize the lane, as well as a space saving arrangement. There are, however, drawbacks to this arrangement. Problems associated with the shared straight/right turn lane system include delays or reduced capacity and road safety due to dangerous maneuvers by road users. Majority of the problem arises from the fact that although the lane serves both through traffic and right turners, the traffic light phases only allows each of them to make their maneuvers during their respective phase. Thus, there will be instances in the phase cycle where a through vehicle cannot move while a right turner can, and vice versa. This would be the main cause of blocking, trapping, and tends to encourage the vehicles behind to pull out of the shared lane. Incidents of horning and pulling out reflect more aggressive driver behavior than normal circumstances dictate and can lead to road safety problems. This is especially true when trapped vehicles try to pull out into an adjacent lane which has moving traffic. Upon careful research and data collection, it was revealed that the arrangement works well during the AM peak hour. As the population of right turners using the shared lane is very high during that period, the shared lane becomes a de facto right turn lane. This generally deters through traffic from using the lane and hence there is usually no problem. The bulk of the issues only occur during the off-peak hour when the right turn population becomes low and the through traffic starts to migrate into the shared lane. Ultimately, as level of service of roads are planned to meet the highest/peak demand, the shared lane can be considered to have served its purpose well. The problems that surface during off-peak hours are not negligible, but the arrangement has overall more pros than cons. Future research can be looked into to alleviate the situation.